LA CALIDAD DE VIDA DEL ADULTO MAYOR DEL HOGAR SOCIAL REINA DEL CISNE, DE LA CIUDAD DE LOJA Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL. - Jara Guarnizo, Nèmesis Eliza (2015)
This research paper entitled "THE QUALITY OF LIFE OF ELDERLY HOME SWAN SOCIAL QUEEN OF THE CITY OF LOJA AND SOCIAL INTERVENTION WORKER" is part of a study at the Social Home of the Swan Queen City Loja; institution with a total of 150 older adults who are cared for in permanent and casual drinks. The care of the elderly is a task that demands human vocation and commitment to the service of those who need to be treated with affection, patience, warmth etc.; tolerating their loss of ability to perform normal daily tasks because of age are naturally becoming difficult to perform with strength usually did. The adult higher today, commonly suffering isolation observed when these faculties are listening clearly, decreased vision or immobility of the lower limbs, have difficulty mobility, isolation with the family group, more even if disease problems arise. These conflicts that surrounds the elderly makes a load of constant attention and care for the family which in many cases suffering trauma is mostly harmful to your health to feel isolated, abandoned, neglected, ignored, lacking affection, forgotten etc., causing them negative feelings and to produce emotional crises of lack of desire to live, low self-esteem, inner suffering. These emotional disorders that can cause them elderly experienced unfavorable states of health and in some cases lead to serious diseases that threaten their normal health and quality of life. In this process or aging stage of every human being, the family group plays an important role, such as the delivery of care and affection, sharing 6 with that being who has given his whole existence take great care every day without measure efforts, regardless of the weather, the cold or the storm that I had to go to feed, clothe, shelter, educate and protect their loved ones. It allows invoke responsibility that the family group, aware of their human duty is a duty to be incredibly wonderful that care is rightfully have been won, and never have been claimed as debt, making it more interesting this family commitment. To be delivered with affection, patience, understanding and companionship in their moments of loneliness pain sadness and joy that still left to live. In the field research data quantitatively and qualitatively what has revealed the problem under study how influences family disintegration in the quality of life of Older Adults Social Home Reina del Cisne city reflected Loja? Where a general objective arises. "Develop a proposal to strengthen the quality of life of seniors. And as a specific objective," theoretically Basing categories of the research problem,” “prepare an assessment of family relationships with the seniors.” “Designing a project social research to strengthen family integration of the Elderly". The methodology used in this research was part of the historical characteristics of an inductive, deductive scientific study, and statistical, that has allowed explain and provide alternative solutions to the problem solution. The results were that., Family breakdown, lack of commitment of the unfamiliar family interest groups and non-participation and exclusion stimulation and the institution generates a weak participation of households in developing activities improve the quality of life of older adults. Home social Swan Queen.